STIMULATING SPEECH DEVELOPMENT THROUGH AUGMENTATIVE AND ALTERNATIVE COMMUNICATION - Цимбал-Слатвінска, Світлана (Modern engineering and innovative technologies, 2024)
The article focuses on the importance of providing information about the effectiveness of AAC techniques, in particular, Laurie Frost and Andy Bondy's PECS system, as an integral mechanism for socialization and improving the quality of life for children,